Fictions : A Selection of Pictures from the 18th, 19th & 20th Centuries - Blau, Douglas; Curt Marcus Gallery, New York (New York : Kent Fine Art Inc., 1987)
Bowman, John ; Ferguson Weir, John ; Hawkes, Howard ; Goldstein, Jack ; Komar & Melamid ; Zwack, Michael ; Hopper, Edward ; etc.
Fictions : A Selection of Pictures from the 18th, 19th & 20th Centuries, Kent Fine Art, New York ; Curt Marcus Gallery, New York, November 17 - December 31, 1987
boek